The Relationship of Academic Stress Levels During Pandemic with Premenstrual Syndrome in Third Grade Senior High School Student - Lestari, Dewi Ayuningrum Puji; Putri, Noviyati Rahardjo; Argaheni, Niken Bayu; Novika, Revi Gama Hatta; Sari, Atriany Nilam (Futurity Medicine, 2024)
Aims: to determine the correlation between academic stress level with premenstrual syndrome in female adolescent. Study design: the employed research method was quantitative observational analysis using a cross-sectional design. Place and Duration of Study: this research was conducted at Senior High School 2 Purworejo, Indonesia, from April to June 2022. Methodology: this research method utilized quantitative observational analysis with a cross-sectional design. Statistical analysis was performed using the Spearman test with a significance level of ρ-value < 0.05. A total of 99 students participated in the study. Results: the result showed that there was a relationship between academic stress levels and premenstrual syndrome (ρ-value<0.05) with strong correlation (r=0.634). Conclusion: there is a clear relationship between academic stress levels with premenstrual syndrome.